2022
DOI: 10.7554/elife.70271
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of stress on feeding behaviors in laboratory mice

Abstract: Stress often affects eating behaviors, increasing caloric intake in some individuals and decreasing it in others. The determinants of feeding responses to stress are unknown, in part because this issue is rarely studied in rodents. We focused our efforts on the novelty-suppressed feeding (NSF) assay, which uses latency to eat as readout of anxiety-like behavior, but rarely assesses feeding per se. We explored how key variables in experimental paradigms – estrous and diurnal cyclicity, age and duration of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…In agreement with our findings, a recent study used novelty-suppressed feeding (NSF) to show that latency to consume food was equally increased in male and female mice, but while novel environment stress reduced food intake in male mice, it had no effect on food intake in female mice [ 17 ]. Furthermore, when rendered obese, both male and female mice displayed hyperphagia in response to novel environment stress [ 17 ]. Interestingly, another study showed the opposite effect, with female, but not male, mice displaying reduced food intake during a novelty-suppressed feeding test [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with our findings, a recent study used novelty-suppressed feeding (NSF) to show that latency to consume food was equally increased in male and female mice, but while novel environment stress reduced food intake in male mice, it had no effect on food intake in female mice [ 17 ]. Furthermore, when rendered obese, both male and female mice displayed hyperphagia in response to novel environment stress [ 17 ]. Interestingly, another study showed the opposite effect, with female, but not male, mice displaying reduced food intake during a novelty-suppressed feeding test [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sex can affect various responses to stress in rodents [ 20 , 23 , 29 , 37 , 56 ], including effects on feeding behavior [ [46] , [67] ]. The directionality of the effect and whether there is even a sex-dependent response to stress depends on the type, duration, and/or intensity of the stressor as well as other factors such as age of the mice and time of day in which the stressor is executed [ 17 ]. In agreement with our findings, a recent study used novelty-suppressed feeding (NSF) to show that latency to consume food was equally increased in male and female mice, but while novel environment stress reduced food intake in male mice, it had no effect on food intake in female mice [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the role of acute stress on motivated reward seeking, we conducted a progressive ratio experiment in a novel environment, a validated model of acute stress that affects feeding (29). Following CNO injections, we observed that active nose pokes were suppressed during the first 5 minutes compared to the home cage (Fig 3M), confirming that acute stress transiently affects motivated reward seeking.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the role of acute stress on motivated reward seeking, we conducted a progressive ratio experiment in a novel environment, a validated model of acute stress that affects feeding (29).Following CNO injections, we observed that active nose pokes were suppressed during the first 5 minutes compared to the home cage ( Interestingly, rearing behavior is typically expressed within a novel environment to survey for potential danger or threat (30). Collectively, these results suggest that mPFC-LH inhibition alleviates the stress-induced decrease in motivation for sucrose pellets and the avoidance of novel food or food presented in a novel environment.…”
Section: Inhibition Of the Mpfc-lh Pathway Increases Food Intakementioning
confidence: 99%